Exploring the Determinants of Instagram as a Social Network for Online Consumer-Brand Relationship - Loureiro, S. M. C.; Sarmento, E. M. (Journal of Promotion Management, 2019)
This study aims at: understanding the influence of the number of followers of the celebrity and the effect of the messages conveyed by them in the intention to buy as well as their intention to create eWoM; studying how the behavior of a celebrity may affect the perception of its credibility, the intention of the consumers to relate to the celebrity in the social networks and the social identification with it; and analyzing the impact of celebrity messages on brands and products that appear in social networks. A convenience sampling method is used to collect a total of 241 responses. This Findings shows that: (i) In terms of intention to purchase, female seem to be more influenced by the opinions and recommendations of celebrities while male tend to be more likely to generate e-word-of-mouth into their contact network through social media. (ii) Regarding to antisocial versus prosocial type of celebrity, celebrities with a prosocial behavior seems to have a greater influence for both genders. (iii) Female tends to feel higher purchase intention when exposed to an endorsement, where celebrity promotes a brand or product through its Instagram account.